Euroscepticism in France: Past and Present - R. I. Blagoveshchenskii (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The United Kingdom European Union membership referendum, victorious for the Brexit supporters, has become one of the most discussed international political events of 2016 and forced policy makers and academics to take a fresh look at prospects of the European integration. In this connection a case of France is of special interest. The author emphasizes that although France was one of the founding members of all European institutions, Paris has always been a difficult partner to Brussels, and Euroscepticism has deep roots in France. The paper examines the genesis and subsequent evolution of the French Euroscepticism and identifies current political positions of the Eurosceptic parties in France. In that context the author emphasizes that Euroscepticism is usually associated with far-right and nationalist political forces but in France it is also represented by left-wing parties. For example, a democratic socialist political party ‘La France Insoumise’, led by Jean-Luc Mélenchon, who won an impressive 18 percent of the votes in the last presidential elections, harshly criticizes Brussel and does not rule out the possibility of France leaving the EU. The paper notes a general trend towards political polarization in the French society, accompanied by strengthening of the non-systemic candidates’ positions. At the same time traditional political parties, such as rightcenter ‘Les Républicains’, seek to adapt to changing preferences of the French electorate. They adopt certain Eurosceptic slogans and strident rhetoric against the EU. The author notes, that in doing so they follow the road travelled by the Conservative Party of Great Britain, which ended up in the European Union membership referendum. The author concludes that Marine Le Pen’s presidential electoral defeat in 2017 does not imply a defeat of the French Euroscepticism. On the contrary, both Eurosceptics and nationalists ceased to be marginalized and have strengthened their positions. Therefore, the possibility of Marine Le Pen’s assumption of the presidency should not be ruled out.